Social Media Management System for Educational Promotion - Singgalen, Yerik Afrianto; Kartikawangi, Dorien; Winayu, Birgitta Narindri Rara (Universitas Bina Darma, 2025)
Educational institutions, particularly tourism study programs, face significant challenges in managing fragmented and inefficient social media promotion strategies that hinder student recruitment and weaken institutional visibility. These problems arise from inconsistent content delivery, lack of stakeholder coordination, and limited performance monitoring and analytics capacity. To address these challenges, this research employs the Rapid Application Development (RAD) methodology through four stages: Requirements Planning, User Design, Construction, and Cutover. The requirement planning phase involved gathering aspirations from all stakeholders within the study program to ensure alignment in designing creative and effective promotional content. The resulting system integrates automated content workflows, scheduling algorithms, demographic-based audience targeting, and real-time performance analytics. The findings indicate substantial improvements in resource efficiency, precision of outreach, enrollment conversion rates, and institutional branding consistency. This research provides a comprehensive framework for transforming academic promotional practices through digital system integration, specifically tailored to the operational needs of educational institutions.